Development of Interactive E-Worksheet Based on Gamification to Improve Digital Literacy of Junior High School Students - Fitrianingsih, Nur; Sani , Khairul; Fitriati , Ita; Shandi , Shutan Arie (Journal of Educational Sciences, 2025)
This research aimed to develop an interactive electronic student worksheet (E-LKPD) based on gamification to enhance the digital literacy of junior high school students. The study was conducted using a Research and Development (R&D) design with the ADDIE model, involving stages of analysis, design, development, implementation, and evaluation. The product was validated by experts in media and material, obtaining feasibility percentages of 92% and 90% respectively, which were categorized as "very feasible." Data were collected through pretest, posttest, and response questionnaires to measure students’ improvement in digital literacy. The results showed an average N-gain score of 0.74, categorized as "high," indicating a significant increase in students’ digital literacy skills after using the developed E-LKPD. Students also responded positively to the interactive features and gamification elements, which increased their engagement and motivation in learning activities. In conclusion, the interactive E-LKPD based on gamification is effective, feasible, and practically applicable for classroom use in improving digital literacy among junior high school students.